2016
DOI: 10.18632/oncotarget.9975
|View full text |Cite
|
Sign up to set email alerts
|

FH535, a β-catenin pathway inhibitor, represses pancreatic cancer xenograft growth and angiogenesis

Abstract: The WNT/β-catenin pathway plays an important role in pancreatic cancer carcinogenesis. We evaluated the correlation between aberrant β-catenin pathway activation and the prognosis pancreatic cancer, and the potential of applying the β-catenin pathway inhibitor FH535 to pancreatic cancer treatment. Meta-analysis and immunohistochemistry showed that abnormal β-catenin pathway activation was associated with unfavorable outcome. FH535 repressed pancreatic cancer xenograft growth in vivo. Gene Ontology (GO) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…As shown in Fig. 3C and D , Rg3 downregulated the Ki-67 level, a major prognostic factor of tumors in general ( 17 ). Immunohistochemical assays further confirmed that Rg3 treatment downregulated the levels of stemness markers, CD24, CD44 and EpCAM, in the orthotopic xenografts ( Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…As shown in Fig. 3C and D , Rg3 downregulated the Ki-67 level, a major prognostic factor of tumors in general ( 17 ). Immunohistochemical assays further confirmed that Rg3 treatment downregulated the levels of stemness markers, CD24, CD44 and EpCAM, in the orthotopic xenografts ( Fig.…”
Section: Resultsmentioning
confidence: 75%
“…IL1A (interleukin 1 alpha) and IL1B (interleukin 1 beta) are members of the interleukin 1 cytokine family, which are involved in various immune responses, inflammatory processes, and hematopoiesis and also play crucial roles in the tumorigenesis of colorectal cancer ( 27 ). IL8 (interleukin 8), PLAUR (plasminogen activator, urokinase receptor), and THPO (thrombopoietin) participate in angiogenesis in a WNT/β-catenin pathway-dependent manner ( 17 ). PGF (placental growth factor) encodes a growth factor found in the placenta that is homologous to VEGF (vascular endothelial growth factor).…”
Section: Discussionmentioning
confidence: 99%
“…CD133 promotes β-catenin signaling and therefore inhibits cancer cell differentiation 37 , and indicates infinitive growth 38 . Besides, it is reported that FH535 represses cancer cell stemness in pancreatic cancer, reducing the CD24+/CD44+ population 14 . Based on the knowledge above, we estimated cancer cell stemness by testing expression of CD24, CD44 and CD133.…”
Section: Discussionmentioning
confidence: 99%
“…FH535 is a dual small molecule inhibitor of peroxisome proliferator-activated receptors (PPARs) and β-catenin/TCF/LEF 10 . Previous studies demonstrated that FH535 inhibits the growth of colon, lung, breast, pancreatic and hepatocellular cancer cells 10 - 13 , and represses pancreatic cancer xenograft growth and angiogenesis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…FH535 is considered as twofold small molecule inhibitor of β-catenin/TCF/LEF and peroxisome proliferator-activated receptors (PPARs) [ 17 ]. Earlier studies revealed that FH535 hampers the growth of colon, lung, breast, hepatocellular cancer cells [ 18 ], and suppresses angiogenesis and pancreatic cancer xenograft growth [ 19 ].…”
Section: Introductionmentioning
confidence: 99%